2022
DOI: 10.3390/nano12101631
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Ferrite–Hydroxyapatite Nanocomposite Synthesis: Biogenic Waste Remodeling for Water Decontamination

Abstract: Environmental pollution, especially water pollution caused by dyes, heavy metal ions and biological pathogens, is a root cause of various lethal diseases in human-beings and animals. Water purification materials and treatment methods are overpriced. Consequently, there is an imperative outlook observance for cheap materials for the purification of wastewaters. In order to fill up the projected demand for clean water, the present study aimed to make use of cost-effective and environmentally friendly methods to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…00-002-0145 with a cubic phase, as indicated by "*" in the XRD pattern. A similar result was observed in the HAP + MnFe 2 O 4 nanocomposite, of which the peaks of MnFe 2 O 4exhibited more with an increase in the additive in the HAP(Algethami et al, 2022).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…00-002-0145 with a cubic phase, as indicated by "*" in the XRD pattern. A similar result was observed in the HAP + MnFe 2 O 4 nanocomposite, of which the peaks of MnFe 2 O 4exhibited more with an increase in the additive in the HAP(Algethami et al, 2022).…”
supporting
confidence: 80%
“…Previous reports generally achieve enhanced photocatalytic and antimicrobial via the hydrothermal approach of the HAP‐MnFe 2 O 4 nanocomposites. These synthesized composite also revealed exceptional bacteriostatic commotion toward S. aureus bacteria and E. coli , which are accountable for acute waterborne infections (Algethami et al, 2022). Khezerlou et al also found that the HAP‐CaFe 2 O 4 composite could be applied as a stimuli responsive carrier for targeted drug delivery and biocompatible application (Khezerlou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Clean and renewable energy, through visible-light-driven photocatalysis, for environmental pollution management is of great interest [23,38]. In comparison to conservative approaches, photocatalysis demonstrates better potential in environmental remediation, owing to price, absence of detrimental derivatives, and durable oxidative competence for pollutants under conventional conditions [39][40][41]. The capacity to integrate the benefits from several facets to act in symphony to accomplish set targets makes composite materials very appealing.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the use of nanomaterials in the biomedical area allows researchers to solve the issues of bacterial antibiotic resistance due to their distinct antibacterial mechanisms. Several metal and metal oxide-based nanomaterials were recently fully integrated into antibacterial applications and demonstrated remarkable performances [ 43 ]. Among them, Ce- and CeO 2 -based nanomaterials garnered a lot of attention across the world.…”
Section: Introductionmentioning
confidence: 99%